PENGARUH TEKNIK PERMAINAN MENYUSUN KATA TERHADAP KEMAMPUAN MEMBACA SISWA DI SANGGAR BIMBINGAN MUHAMMADIYAH KEPONG MALAYSIA - silvia, tiara; Sari, Suci Perwita (JRPD (Jurnal Riset Pendidikan Dasar), 2025)
The main problem in this research is how to improve students' reading skills through word composing game techniques for class II elementary school at sanggar bimbingan muhammadiyah kepong Malaysia.The aim of this research is to determine the effect of word composing game techniques on students' reading abilities in the Muhammadiyah Kepong Malaysia guidance studio in learning Indonesian. This type of research uses experimental research with a quantitative approach. This research was carried out using expert validity (Expert judgment) and hypothesis testing. The population in this study were all class II students at sanggar bimbingan muhammadiyah kepong Malaysia.totaling 10 students using the experimental method. The research instruments used were performance tests and documentation. The data collection techniques in this research are expert validity testing (Expert Judgment) and hypothesis testing. The collected data was then analyzed using quantitative analysis. The results of this research showed that the average results of students' reading abilities increased significantly after learning using the word composing game technique.  This is shown by the pretest average of 69.25 and the posttest average of 88.25. This difference shows that there is an increase in students' reading abilities. Thus, the results of the research can be concluded that the